KEBIJAKAN HUKUM PENATAAN KURIKULUM MATA KULIAH KEWARGANEGARAAN DI PERGURUAN TINGGI GUNA REVOLUSI KARAKTER MENTAATI HUKUM BAGI MAHASISWA - Hassan Suryono (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2016)
The purpose of this paper is to build a model realignment curriculum courses of study materials Citizenship in Higher Education to be optimized to develop character in the students obey the law. Character is rooted in the principle of the Deity, Humanity, Unity, Democracy and Justice. These characters can only be fulfilled if every law-abiding citizen. To achieve this required observance of exemplary education providers. Structuring the curriculum in this first formulate the vision, mission and goals of citizenship course, determine the profiles and the formulation of competence and competence synchronize efforts with the study material. Citizenship material substance awareness and observance of the law is derived from the principle of divinity, humanity, unity, democracy and justice and includes the study of God's law, the law of Nature and the ethical and legal principles of the positive law of Indonesia. Positive law in question is the contextual Regulations Invite occurring in the community / region / town and village. Structuring the study material of citizenship in the legal aspect is emphasized in addition to the legal knowledge, content, attitudes and behavioral patterns of law, but also the values of law / Act. So the emphasis on stransfer legal value and not solely the transfer of legal knowledge. Follow-up of the implementation of the study need to be tested in the learning process on campus, as well as extra-curricular activities laboratory practice can be done both on campus and off-campus universities in accordance with their respective capabilities.